Electrophoresis Studies of Ranunculus triplodontus Populations - SURANTO SURANTO (Society for Indonesian Biodiversity, 2000)
The main purposes of this research were to investigate whether the two distinct types of the morphological characterof Ranunculus triplodontus were genetically controlled or environmental influence. In order to prove the above,electrophoretic examinations were carried out employing for four enzyme systems. The medium support of polyacrilamide was chosen. The samples were collected from seven populations around central plateau and the leaves were used as the isozyme data. The result indicated that variation occurred in certained populations. However, this isozyme data were not able to separate the two types of R. triplodontus into different species. Based on the cluster analysis showed that three groups of seven populations of R. triplodontus were appeared. This research confirms that morphologically distinct species was not supported by the isozyme data, thus the variation found in certain population was mainly influenced by the environmental conditions, and therefore could not be considered as taxonomically distinct.Â© 2001 Jurusan Biologi FMIPA UNS SurakartaKey words: Ranunculus triplodontus, isozyme.